Algas verdes cocóides (Chlorophyta) de duas áreas do Pantanal dos Marimbus (Baiano e Remanso), APA Marimbus-Iraquara, Chapada Diamantina, Bahia, Brasil - Ramos, Geraldo José Peixoto (2013)
This study aimed at surveying the coccoid green algae flora of two areas of the Pantanal dos Marimbus (Baiano and Remanso), EPA Marimbus Iraquara, located in the Chapada Diamantina, Bahia, Brazil. Material was obtained from 120 samples collected during the dry (April, June and August 2011) and in the rainy season (October and December 2011, and February 2012). During this study 121 taxa of coccoid green algae were identified, described, illustrated and commented, which are distributed in two classes, four orders and 46 genera, 109 species, three varieties typical and seven other does not typical of their respective species, and two taxonomic formae. 17 (14%) of the total of taxa identified are pioneer citations for Brazil, 51 taxa (42%) for the Northeast Region of Brazil, and 19 taxa (15,7%) for the Bahia State. Most taxa recorded were classified in the Sphaeropleales (76%), followed by Chlorellales (17%), Trebouxiales (3%) and Chlorococcales ‘sensu stricto’ (2%), while the taxa considered ‘incertaesedis’ were represented by 3% of the total taxa identified. Among the taxa studied in both areas, 14 were exclusive of the rainy period and only seven of the dry one, while 100 taxa were common to both climatic periods. The species richness was clearly higher in the Marimbus do Baiano with 115 taxa (95%), while the Marimbus do Remanso showed 99 taxa (82.5%). Of the 121 taxa studied, 22 were unique to the Marimbus do Baiano and six to the Marimbus do Remanso. According to the Sörensen similarity index (86.9%), the similarity between the Marimbus do Baiano and do Remanso was considered high. Most taxa inventoried (48%) was classified as rare on Pantanal Marimbus, followed by infrequent (42%), frequent (7%) and very frequent (3%). Considering that about 90% of the taxa found are listed first for the Bahia State, we strongly suggest continuing studies of biodiversity of inland water algae to increase knowledge of phycoflora in Bahia State and Brazil.